2007
DOI: 10.1002/asi.20681
|View full text |Cite
|
Sign up to set email alerts
|

Relevance: A review of the literature and a framework for thinking on the notion in information science. Part III: Behavior and effects of relevance

Abstract: Relevance is a, if not even the, key notion in information science in general and information retrieval in particular. This two-part critical review traces and synthesizes the scholarship on relevance over the past 30 years or so and provides an updated framework within which the still widely dissonant ideas and works about relevance might be interpreted and related. It is a continuation and update of a similar review that appeared in 1975 under the same title, considered here as being Part I. The present revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
222
0
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(242 citation statements)
references
References 74 publications
7
222
0
13
Order By: Relevance
“…A key notion in the field of information retrieval but also in information science in general is that of relevance [9] whose definition has stimulated widely dissonant ideas and works. As introduced in Sect.…”
Section: State Of the Artmentioning
confidence: 99%
“…A key notion in the field of information retrieval but also in information science in general is that of relevance [9] whose definition has stimulated widely dissonant ideas and works. As introduced in Sect.…”
Section: State Of the Artmentioning
confidence: 99%
“…While, in general, the order of results might have influenced the judgments (Bar-Ilan et al, 2009;Joachims et al, 2007), it has been shown that when the number of results is small than this influence is insignificant (Saracevic, 2007).…”
Section: Presentation Biasmentioning
confidence: 99%
“…As stated by (Saracevic, 2007(Saracevic, , p. 2139: "The role of research is to make relevance complexity more comprehensible formally and possibly even more predictable". Accurate ranking of search results according to the users' preferences is one of the most important challenges of the modern search systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing a document as relevant to an information need can be a complex decision that may be affected by the searcher's knowledge, the task being conducted, the collection being searched, the retrieval results and properties of the document itself (Barry and Schamber, 1998;Harter, 1996;Ruthven, 2005;Saracevic, 2007a;Saracevic, 2007b;Spink et al, 1998;Vakkari and Hakala, 2000;Voorhees, 2001). Analysing relevance assessments can help us understand how people make judgments about relevance, how people solve information problems and, through collection of assessments within test collections, help us evaluate the performance of retrieval systems.…”
Section: Introductionmentioning
confidence: 99%